A compact high-energy particle detector for low-cost deep space missions - Kemp, Dayne Hilton (Department of Electrical Engineering, 2016)
Over the last few decades particle physics has led to many new discoveries, laying the foundation for modern science. However, there are still many unanswered questions which the next generation of particle detectors could address, potentially expanding our knowledge and understanding of the Universe. Owing to recent technological advancements, electronic sensors are now able to acquire measurements previously unobtainable, creating opportunities for new deep-space high-energy particle missions. Consequently, a new compact instrument was developed capable of detecting gamma rays, neutrons and charged particles. This instrument combines the latest in FPGA System-on-Chip technology as the central processor and a 3x3 array of silicon photomultipliers coupled with an organic plastic scintillator as the detector. Using modern digital pulse shape discrimination and signal processing techniques, the scintillator and photomultiplier combination has been shown to accurately discriminate between the di_erent particle types and provide information such as total energy and incident direction. The instrument demonstrated the ability to capture 30,000 particle events per second across 9 channels - around 15 times that of the U.S. based CLAS detector. Furthermore, the input signals are simultaneously sampled at a maximum rate of 5 GSPS across all channels with 14-bit resolution. Future developments will include FPGA-implemented digital signal processing as well as hardware design for small satellite based deep-space missions that can overcome radiation vulnerability.